(untitled) (Jurnal Bahasa, 2006)
This study is a general survey on the various aspects of Kayan language carried out in Belaga and Miri. This brief study is more concentrated on the linguistic aspects, i.e. to observe the linguistic behaviour and origin of a certain native language, especially in Sarawak This study also tried to reveal the phonology, morphology and syntactic patterns of Kayan language used by the communicating community. Besides, this study also gave a brief view of social cultural behaviour of the Kayan tribe in Sarawak.